2020
DOI: 10.3389/fmed.2020.00440
|View full text |Cite
|
Sign up to set email alerts
|

Early Weight-Based Aggressive vs. Non-Aggressive Goal-Directed Fluid Resuscitation in the Early Phase of Acute Pancreatitis: An Open-Label Multicenter Randomized Controlled Trial (The WATERFALL Trial), Design, and Rationale

Abstract: Treatment options are limited for acute pancreatitis (AP). Early aggressive fluid resuscitation (AFR) has been widely considered beneficial because of theoretical improvement in end-organ perfusion, including the pancreas and gut, with pancreatic necrosis and bacterial translocation as consequences of ischemia. There is scarce direct evidence for its association to improved outcomes. Furthermore, it has been described that AFR may be associated with poor outcomes in severe AP. WATERFALL is an investigator-init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The aggressive arm received 20 mL/kg bolus-administered over 2 h, followed by 3 mL/kg/h for 12 h-vs. a moderate arm receiving a bolus 10 mL/kg-administered over 2 h in case of hypovolemia or no bolus in patients with normovolemia, followed by 1.5 mL/kg/h for 12 h; afterward, all patients with normovolemia received 1.5 mL/kg/h. The final results of this trial will be available in the following weeks (accepted, under press embargo) [85].…”
Section: Management Of Pepmentioning
confidence: 99%
“…The aggressive arm received 20 mL/kg bolus-administered over 2 h, followed by 3 mL/kg/h for 12 h-vs. a moderate arm receiving a bolus 10 mL/kg-administered over 2 h in case of hypovolemia or no bolus in patients with normovolemia, followed by 1.5 mL/kg/h for 12 h; afterward, all patients with normovolemia received 1.5 mL/kg/h. The final results of this trial will be available in the following weeks (accepted, under press embargo) [85].…”
Section: Management Of Pepmentioning
confidence: 99%
“…For example, acute kidney injury was suggested as an indicator of hypovolemia in the WATERFALL trial and was reported to be related to acute kidney injury in previous studies. [19,36] Central venous pressure (CVP) seemed to be a considerable indicator of hypovolemia in AP, especially SAP. [37][38][39] Finally, we did not discuss other factors of fluid resuscitation, such as different routes and types of fluids due to a lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed criteria for fluid overload and hypovolemia were based on previous studies. [18,19] Secondary outcomes…”
Section: Primary Outcomesmentioning
confidence: 99%
“…There is increasing research in the field of molecular diagnostics for pancreatobiliary diseases such as pancreatic cancer (addressed in the oncology section) and pancreatic cysts. National and international multicentre trials are being developed for Viewpoint the treatment of acute and chronic pancreatitis, 53,54 following a successful model of collaborative research designed by the Dutch Pancreatitis Study Group. 55…”
Section: Pancreatology and Biliary Diseases Strengthsmentioning
confidence: 99%